COMMUNITY ENGAGEMENT PLAN ONLINE STUDENTS HELP FOR INDONESIAN SCHOOL IN RIYADH, SAUDI ARABIA - Dwi Nisa Widhawati (Journal of Management and Social Sciences, 2022)
Indonesian School in Riyadh (ISR) was established in 1985 by Indonesian embassy in Riyadh in purpose to accommodate the students from Kindergarten to Year 12. The school educates students in three languages: Indonesian, Arabic and English (Setyono, 2016). The ISR has no selection system on students’ competencies for enrolment process like in the home country. The school is only one option for Indonesian children in Riyadh where students from various backgrounds are accepted. Online students’ help is design eLearning in purpose to improve students’ achievement.